Role of Total Carnitine to Free Carnitine Ratio (TC/FC) in Monitoring Outcome of Haemodialysis - Shaukat, Danya (International Journal of Pathology, 2022)
Carnitine, a quaternary ammonium compound actively involved in beta peroxidation of fatty acids isdocumented to be lost in excess in patients of chronic kidney disease (CKD) especially in those undergoing MHD,this loss is attributable to malfunctioning of kidneys and being washed away by dialytic sessions. This decrease isattributable to most of the complications encountered in these patients.Objective: To measure carnitine levels (total and free) in patients on dialysis in comparison with healthy controls To determine total versus free carnitine ratio (TC/FC), for detecting accumulation of carnitinemetabolites.Materials and Methods: This Observational Cross-sectional study was conducted in the department ofchemical pathology (AFIP), in collaboration with Armed forces institute of Urology (AFIU) from August 2020 toJanuary 2021. Non probability convenient sampling technique was employed for sampling. All individualsundergoing dialysis for duration ≥6 months were enrolled in case cohorts. Carnitine (free and total) levels weredetermined by using human bioassay ELISA kits and their ratios were calculated for comparison.Results: 160 participants were enrolled in study subdivided as diabetic and non-diabetic groups with 1:1 male tofemale ratio. TC/FC ratio was found to be high in case group, in comparison with control group. A rising trend ofratios was observed with increasing duration of dialysis.Conclusion: TC/FC ratio was high in dialysis patients suggestive of carnitine metabolite accumulation,suggesting that efficacy of dialysis should be promptly monitored on the basis of TC/FC ratio for early detectionof complications secondary to carnitine metabolites accumulation